2013
DOI: 10.5433/1679-0359.2013v34n4p1451
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de defensivos agrícolas naturais e extratos vegetais sobre parâmetros biológicos de Metarhizium anisopliae (Metsch.) Sorok

Abstract: Efeito de defensivos agrícolas naturais e extratos vegetais sobre parâmetros biológicos de AbstractThis study was carried out aiming to evaluate the effect and compatibility of vegetal and Pycnoporus sanguineus basidiocarps extracts and alternative products on biological parameters of Metarhizium anisopliae fungus. Extracts (solution in water 10%) and natural products (AR = average field recommendation; 0.5 AR and 2.0 AR) are applied on PDA culture media surface previously inoculated with fungi conidia. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
1
12
0
1
Order By: Relevance
“…Viability of conidia, colony forming units, vegetative growth, conidia production, "T" values and compatibility of Metarhizium anisopliae (UNIOESTE 22) subjected to different homeopathic medicines (26 ± 1°C and 12-h photophase). This increase in CFU is a trend already observed by other authors in analyses of NP (commercial products, aqueous and alcoholic plant extracts) and biological parameters of M. anisopliae, which can likely be attributed to the degradation and utilization of substances present in the composition of products tested and may have been used as nutrients by the fungus Mamprim et al, 2013).…”
Section: Treatmentssupporting
confidence: 59%
See 1 more Smart Citation
“…Viability of conidia, colony forming units, vegetative growth, conidia production, "T" values and compatibility of Metarhizium anisopliae (UNIOESTE 22) subjected to different homeopathic medicines (26 ± 1°C and 12-h photophase). This increase in CFU is a trend already observed by other authors in analyses of NP (commercial products, aqueous and alcoholic plant extracts) and biological parameters of M. anisopliae, which can likely be attributed to the degradation and utilization of substances present in the composition of products tested and may have been used as nutrients by the fungus Mamprim et al, 2013).…”
Section: Treatmentssupporting
confidence: 59%
“…Accordingly, it was found that some commercial products such as Ecolife® and Stubble-Aid® and others neem-oil-based affected conidia production and the vegetative growth of M. anisopliae (Marques et al, 2004;. Mamprim et al (2013) highlighted the negative effect of lime sulfur broth on all biological parameters of M. anisopliae, classified as moderately toxic. However, the same authors have shown that aqueous and alcoholic plant extracts of some insecticide plants have proved compatible to the fungal development.…”
Section: Introductionmentioning
confidence: 99%
“…After this period, filtering was performed in sterile cotton gauze and filter paper, and then the filtrate liquid was maintained at -10 °C (Mamprim et al, 2013).…”
Section: Product and Extracts Usedmentioning
confidence: 99%
“…Following this distilled water was added in a waste weight/volume ratio to obtain a 10% concentration. Subsequently, vacuum sterilization was performed with a 0.45 mm pore membrane and the material was stored at -10 °C (Mamprim et al, 2013).…”
Section: Product and Extracts Usedmentioning
confidence: 99%
See 1 more Smart Citation